Analisis Strategi Bersaing Toko Oleh-Oleh UD Purnama Jati Jember - Hanindita Febriana Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to determine and explain the competitive strategies used by UD Purnama Jati in facing competitive business competition. This research uses a qualitative method with a descriptive approach. Data were collected through interviews, observation, and documentation. Data analysis used domain and taxonomy analysis. The results showed that Porter's Five Forces model helped UD Purnama Jati in analyzing competitive conditions. In addition, UD Purnama Jati has also implemented Porter's Three Generic Strategies, namely low cost leadership, differentiation, and focus. The low cost leadership strategy is carried out by production efficiency, long-term cooperation with suppliers, and competitive prices. The differentiation strategy is carried out by providing diverse products, maintaining quality, and providing offline and online services. The focus strategy is carried out by targeting the family, student and agency segments. The combination of the three strategies strengthens the company's market position and increases value for customers.
Reuploud file repositori 28 Januari 2026_Yudi
Keywords: Competitive strategy; Five Forces Porter; Generic Strategy Porter